2020
DOI: 10.7717/peerj.9957
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dynamic and widespread lncRNA and miRNA expression in fetal sheep skeletal muscle

Abstract: The sheep is an economically important animal, and there is currently a major focus on improving its meat quality through breeding. There are variations in the growth regulation mechanisms of different sheep breeds, making fundamental research on skeletal muscle growth essential in understanding the regulation of (thus far) unknown genes. Skeletal muscle development is a complex biological process regulated by numerous genes and non-coding RNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In addition, Chao et al sequenced the longissimus dorsi muscles of sheep from the 60, 90, and 120th days of pregnancy and the 0 and 360th days after birth and identified the differentially expressed miR-433. These findings suggest that miR-433 might affect sheep skeletal muscle development by regulating myogenic differentiation ( 39 ). Qin et al found that the overexpression of miR-22-5p in rat cardiomyocytes can affect the RAP1/ERK pathway and cardiomyocyte apoptosis ( 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Chao et al sequenced the longissimus dorsi muscles of sheep from the 60, 90, and 120th days of pregnancy and the 0 and 360th days after birth and identified the differentially expressed miR-433. These findings suggest that miR-433 might affect sheep skeletal muscle development by regulating myogenic differentiation ( 39 ). Qin et al found that the overexpression of miR-22-5p in rat cardiomyocytes can affect the RAP1/ERK pathway and cardiomyocyte apoptosis ( 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…Since the number of myotubes is constant before birth, we focus on miRNAs with low expression before birth and high expression after birth. MiR-22-3p has been detected in the longissimus dorsi muscle of sheep and the expression of miR-22-3p is the lowest at 60 days of pregnancy and the highest at 360 days after birth [ 10 ]. Cancer literatures proved that miR-22-3p targets SP1 , inhibits the expression of downstream genes CCND1 and BCL2 , thereby inhibiting the growth of liver cancer cells, and the low expression of miR-22-3p is associated with metastatic liver cancer [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-22-3p has been found as one of the differentially expressed miRNAs during Hu sheep muscle development [ 10 ]. A recent study showed that miR-22-3p treats fibrous cataract by targeting HDAC6 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, research into expression profiles of miRNAs in the skeletal muscle tissue of domestic animals have mainly been focused on pigs ( 6 – 9 ), cattle ( 10 13 ), and sheep ( 14 17 ). It was found from these studies described above that miRNAs were differentially expressed in skeletal muscle at different developmental periods, or between different breeds.…”
Section: Introductionmentioning
confidence: 99%